The Impact of Bullying on a Child’s Development: A Gender Based Analysis - Dr. Namita Verma; Dr. Ruchi Tewari (International Journal on Orange Technologies, 2022)
It probably comes as no surprise, but bullying has been linked to an enormous amount of developmental issues in children – both in those who have been bullied and those who have bullied others. In fact, according to the National Institute of Child Health and Human Development (NICHD), bullying has a lifelong impact on the social and emotional development of children that puts them at risk for everything from severe mental health issues to stunted professional growth later in life. According to the NICHD, children who are involved in bullying experiences (on either side of the situation) are at an increased risk of developing issues such as: Depression and anxiety Low self-esteem and personal drive Trouble focusing and falling grades Behavioral problems Social and relationship issues Substance abuse later in life Self-harming behaviors Bullying can also affect other children who witness the acts – even if they aren’t directly involved – by leaving them feeling insecure in their environments and fearing they could be next. The long-term effects of bullying go well beyond the initial instances and the people at the center of it and can often stay with a person for the remainder of their life. Since bullying can essentially destroy a child’s self-esteem, it can manifest itself in ways that will jeopardize future opportunities for years to come.